Cardiotrophin-1 Induces Tumor Necrosis Factor α Synthesis in Human Peripheral Blood Mononuclear Cells - Fritzenwanger, Michael (Hindawi Publishing Corporation, 2009)
Chronic heart failure (CHF) is associated with elevated concentrations of tumor necrosis factor (TNF) α and cardiotrophin-1 (CT-1) and altered peripheral blood mononuclear cell (PBMC) function. Therefore, we tested whether CT-1 induces TNFα in PBMC of healthy volunteers. CT-1 induced in PBMC TNFα protein in the supernatant and TNFα mRNA in a concentration- and time-dependent manner determined by ELISA and real-time PCR, respectively. Maximal TNFα protein was achieved with 100 ng/mL CT-1 after 3–6 hours and maximal TNFα mRNA induction after 1 hour. ELISA data were confirmed using immunofluorescent flow cytometry. Inhibitor studies with actinomycin D and brefeldin A showed that both protein synthesis and intracellular transport are essential for CT-1 induced TNFα expression. CT-1 caused a dose dependent nuclear factor (NF) κB translocation. Parthenolide inhibited both NFκB translocation and TNFα protein expression indicating that NFκB seems to be necessary. We revealed a new mechanism for elevated serum TNFα concentrations and PBMC activation in CHF besides the hypothesis of PBMC activation by bacterial translocation from the gut.